Nipple Drinkers for Brooding Commercial Large White Turkeys - Russell, S.M.; Grimes, J.L.; Gernat, A.G. (International Journal of Poultry Science, 2009)
The objective of this research was to determine the effect of using nipple drinkers during brooding on the performance of Large White turkeys. There were 6 different drinkers tested: the control and 5 nipple drinker systems. The control was the Plasson Drinker and the nipple systems tested were the Plasson Easy Start (PES), Val-Co Turkey Drinker (VC), Lubing Traditional Nipple (LTN), Lubing EasyLineTM (LEL) and Ziggity Big-Z Activator (BZ). Three experiments were conducted with turkeys brooded using the 6 drinker types. Some nipple drinker treatments were used in the rearing periods. At 20 wk, Body Weight (BW) was reduced for toms brooded to 6 wk on the LTN and brooded and reared on the VC. The use of LEL and LTN (during brooding) resulted in improved Feed Conversion (FC) at 20 wk. Trial 2-experiment 1 with hens of two strains was terminated at 3 wk because of excessive mortality from dehydration with some drinker types. In trial 2 -experiment 2, there were no poult hydration issues. The BW of hens at 6 wk brooded on the Plasson Drinker and the VC were higher compared to the BW of hens brooded on the PES and the BZ with the BW of hens on the LEL being intermediate. The use of the LTN resulted in significantly lower hen BW compared with all other drinkers through 10 wk. By 16 wk, there were no longer differences in hen BW due to drinker type. Drinker type did not have an effect on hen FC. Nipple drinkers can be used effectively to brood turkeys with some types also being useful during the rearing period. However, poor quality, inactive, or diseased poults may be at risk for dehydration on some nipple drinker systems.